The Effects of Ownership and Corporate Governance Reforms on Efficiency of Privatized Companies in Kenya - Gitundu, Esther Wanjugu; Kisaka, Sifunjo E.; Kiprop, Symon Kibet; Kibet, Lawrence Kangogo (International Journal of Economics and Financial Issues, 2016)
This study investigated the effects of ownership and corporate governance reforms on efficiency of privatized companies in Kenya for the period 2007-2013. Data was extracted from financial reports. A unit root test examined stationarity of data. A fixed effects regression model with a robust standard error option was used to control for firm specific effects which could bias results. The results indicate government ownership has a negative effect on cost and technical efficiency. Local institutional investors influence technical efficiency positively. Large individual shareholders have a positive influence on cost efficiency while dispersed ownership influence cost efficiency negatively. Both non-executive and women directors influence cost efficiency positively. This study recommends further reduction of state and dispersed ownership to pass more ownership and control to institutional investors. Diversity in corporate boards should be enhanced to enable firms to attract managerial and technical expertise from the non -executive and women directors. Keywords: Privatization; SOEs; Efficiency JEL Classifications: G32, H21